Differential skeletal response in adult and aged rats to independent and combinatorial stimulation with pulsed electromagnetic fields and mechanical vibration. Issue 2 (29th December 2019) - Cai, Jing; Shao, Xi; Yan, Zedong; Liu, Xiyu; Yang, Yongqing; Luo, Erping; Jing, Da
Abstract: Pulsed electromagnetic fields (PEMFs) and whole‐body vibration (WBV) are proved to partially preserve bone mass/strength in hindlimb‐unloaded and ovariectomized animals. However, the potential age‐dependent skeletal response to either PEMF or WBV has not been fully investigated. Moreover, whether the coupled "mechano‐electro‐magnetic" signals can induce greater osteogenic potential than single stimulation remains unknown. Herein, 5‐month‐old or 20‐month‐old rats were assigned to the Control, PEMF, WBV, and PEMF + WBV groups. After 8‐week treatment, single PEMF/WBV enhanced bone mass, strength, and anabolism in 5‐month‐old rats, but not in 20‐month‐old rats. PEMF + WBV induced greater increase of bone quantity, quality, and anabolism than single PEMF/WBV in young adult rats. PEMF + WBV also inhibited bone loss in elderly rats by primarily improving osteoblast and osteocyte activity, but had no effects on bone resorption. PEMF + WBV upregulated the expression of various canonical Wnt ligands and downstream molecules (p‐GSK‐3β and β‐catenin), but had no impacts on noncanonical Wnt5a expression in aged skeleton, revealing the potential involvement of canonical Wnt signaling in bone anabolism of PEMF + WBV. This study not only reveals much weaker responsiveness of aged skeleton to single PEMF/WBV relative to young adult skeleton, but also presents a novel noninvasive approach based on combinatorial treatment with PEMF + WBV for improving bone health and preserving bone quantity/quality (especially for age‐related osteoporosis) with stronger anabolic effects.